Structure of glutathione S‐transferase 1 from the major human hookworm parasite Necator americanus (Na‐GST‐1) in complex with glutathione. Issue 9 (1st September 2014) - Asojo, Oluwatoyin A.; Ceccarelli, Christopher
<x xml:space="preserve">Abstract</x> Glutathione S‐transferase 1 from Necator americanus (Na‐GST‐1) is a vaccine candidate for hookworm infection that has a high affinity for heme and metal porphyrins. As part of attempts to clarify the mechanism of heme detoxification by hookworm GSTs, co‐crystallization and soaking studies of Na‐GST‐1 with the heme‐like molecules protoporphyrin IX disodium salt, hematin and zinc protoporphyrin were undertaken. While these studies did not yield the structure of the complex of Na‐GST‐1 with any of these molecules, co‐crystallization experiments resulted in the first structures of the complex of Na‐GST‐1 with the substrate glutathione. The structures of the complex of Na‐GST‐1 with glutathione were solved from pathological crystalline aggregates comprising more than one crystal form. These first structures of the complex of Na‐GST‐1 with the substrate glutathione were solved by molecular replacement from data collected with a sealed‐tube home source using the previously reported apo structure as the search model.